INVESTIGATION OF THE PARAMETERS OF RAILWAY STATIONS USING PETRI NETS - Demchenko, Y. B.; Malashkin, V. V.; Skovron, I. Y. (Science and Transport Progress, 2020)
Purpose. The work is aimed to determine the rational parameters of a railway station based on the simulation modeling of its functioning process, presented by the Petri net in QPNet using the proposed methodology of technical and economic comparison of equipment options. Methodology. The authors presented a methodology for formalizing the functioning of the sorting complex using a Petri net in QPNet. Particular attention is paid to the formalization of the operation of the hump locomotive. Methodology of technical and economic comparison of equipment options for the sorting complex was developed. It is based on the use of modified summarized costs. Findings. The authors performed a review of existing simulation systems, which can be specialized and universal. Specialized ones have richer display capabilities, allow you to create models for specific objects faster and more accurately, and as a result you can get the best set of results with their help. At the same time, the universal systems gained greater recognition, despite the requirement of some refinement and adaptation to a specific process, since specialized simulation systems are paid or insufficiently advertised, which does not allow a wide circle of researchers to use them to solve the set tasks. The paper presents the operation results of sorting complex with various equipment, obtained by simulation in the QPNet. The obtained values of the technical and technological parameters of the sorting complex became the basis for determining rational measures aimed at improving the efficiency of the sorting station in various operating conditions. Originality lies in improving the simulation model of the sorting complex which functioning is represented by the temporary Petri net. This, unlike other models, allows you to take into account the additional time of hump locomotive occupation by other operations not directly related with trains breaking-up. Practical value of the improved simulation model of the sorting complex presented in the work lies in the ability to more accurately take into account the influence of the technical equipment parameters of the railway station on its performance.